War during Childhood: The Long Run Effects of Warfare on Health - Mevlude Akbulut-Yuksel (Institute of Labor Economics (IZA), 2017)
This paper estimates the causal long-term consequences of an exposure to war in utero and during childhood on the risk of obesity and the probability of having a chronic health condition in adulthood. Using the plausibly exogenous city-by-cohort variation in the intensity of WWII destruction as a unique quasi-experiment, I find that individuals who were exposed to WWII destruction during the prenatal and early postnatal periods have higher BMIs and are more likely to be obese as adults. I also find an elevated incidence of chronic health conditions such as stroke, hypertension, diabetes, and cardiovascular disorder in adulthood among these wartime children.
Keywords: I10; I12; J13; 330; health conditions; body size; warfare; children